ELEMENTS INFLUENCING VIRTUAL FOOD DISTRIBUTION FACILITY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This abstract examines the different elements influencing online meal delivery businesses. The many factors affecting online food delivery services are examined in this abstract. It draws attention to how crucially competitive dynamics, technical advancements, legal frameworks, and customer preferences shape the economic sustainability and durability of these platforms. The study emphasizes the importance of elements including food quality, user experience, technological integration, regulatory compliance, and market rivalry by examining the body of existing literature and empirical data. In order to improve customer satisfaction, operational efficiency, and long-term viability in the dynamic and competitive Industry of food, networks for internet delivery of food have to recognize and take action on these elements.